A descriptive analysis of extended matching questions among third year medical students - Vuma, Sehlule; Sa, Bidyadhar (International Journal of Research in Medical Sciences, 2017)
Background: With changes in teaching methods in medicine, assessment tools have also evolved in order to be valid, reliable, practical, analyzable and not time-consuming. After questions of reliability and practicality when using free response short answer questions, we replaced them with extended matching questions (EMQs). Previous analysis of the same group of students, in the same time period, showed high reliability and discrimination with standard multiple choice questions (MCQ). Objective was to describe the efficiency of Extended matching questions (EMQ) in third-year medicine courses Methods: Castler-Rock Integrity programme, item analyzed reports of EMQ results over a three-year period were analyzed. There were 25EMQ items in each course, each year, with 9 option answers. Results: The Kuder Richardson-20 reliability mean ranged from 0.447 to 0.674. Spearman-Brown split half-reliability coefficient mean ranged from 0.443 to 0.685. Spearman-Brown prophecy reliability formula mean from 0.614 to 0 837. The Guttman split-half reliability coefficient mean ranged from 0.441 to 0.718. The difficulty mean ranged from 0.491 to 0.719. The Corrected point bi-serial coefficient ratio mean was 0.118 to 0.255. The number of items with all-functioning distractors ranged from 16% to 40%, and the total number of non-functioning distractors ranged from 14.5% to 28%. Conclusions: EMQs showed reliability, though lower than with the MCQs previously analyzed. This may be due to the much smaller numbers hence increasing numbers of EMQs should be considered. There was a high number of functioning distractors. Poor distractors should be revised.